Proposed 1982 outer Continental shelf oil and gas lease sale offshore the North Atlantic states, OCS sale no. 52 - United States. New York Outer Continental Shelf Office. ([New York, N.Y.] : The Office, 1981)
Final environmental impact statement. [v.1] Draft environmental impact statement -- [v.2] Mode of access: Internet.